Carbon cycling in Anabaena sp. PCC 7120. Sucrose synthesis in the heterocysts and possible role in nitrogen fixation - Cumino, Andrea Carina (2007)
Nitrogen (N) available to plants mostly originates from N2 fixation carried out by prokaryotes. Certain cyanobacterial species contribute to this energetically expensive process related to carbon (C) metabolism. Several filamentous strains differentiate heterocysts, specialized N 2-fixing cells. To understand how C and N metabolism are regulated in photodiazotrophically grown organisms, we investigated the role of sucrose (Suc) biosynthesis in N2 fixation in Anabaena sp. PCC 7120 (also known as Nostoc sp. PCC 7120). The presence of two Suc-phosphate synthases (SPS), SPS-A and SPS-B, directly involved in Suc synthesis with different glucosyl donor specificity, seems to be important in the N2-fixing filament. Measurement of enzyme activity and polypeptide levels plus reverse transcription-polymerase chain reaction experiments showed that total SPS expression is greater in cells grown in N2 versus combined N conditions. Only SPS-B, however, was seen to be active in the heterocyst, as confirmed by analysis of green fluorescent protein reporters. SPS-B gene expression is likely controlled at the transcriptional initiation level, probably in relation to a global N regulator. Metabolic control analysis indicated that the metabolism of glycogen and Suc is likely interconnected in N2-fixing filaments. These findings suggest that N2 fixation may be spatially compatible with Suc synthesis and support the role of the disaccharide as an intermediate in the reduced C flux in heterocyst-forming cyanobacteria. © 2007 American Society of Plant Biologists.